PEMBERDAYAAN MASYARAKAT NAGARI PERSIAPAN GIRI MAJU, KABUPATEN PASAMAN BARAT DENGAN INOVASI DAN TEKNOLOGI PENGOLAHAN JAGUNG - P.K. Dewi Hayati; Siska Efendi; Ira Desri Rahmi; Rafki Saputra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Maize is the main cash crop in intercropping system applied for replanting of palm oil which is expected to be the main source of income before palm oil crops produce. The transfer of maize cultivation technology in small holder palm oil plantation is aimed at increasing production of maize without harming the main crops and maintaining the productivity of land and the environment. Increased income can also be done through efforts to increase the added value of maize seeds into various food products. KKN-PPM activities that took place in Nagari Persiapan Girimaju, Luhak Nan Duo sub-district, West Pasaman district from June to August 2018 aimed to transfer maize production technology that is environmentally friendly and to transfer knowledge and skills in increasing the value added of maize into various food and other processed products. Results obtained from the KKN activities were (1) the community was able to apply maize production technology which was synergized with cattle farming, (2) there was an increase in the efficiency of maize production through introduction of maize sheller machine, (3) the community was able to produce a variety of maize-based food products and ( 4) the formation of new UMKMs in the location. The results of statistical analysis using a Likert scale gave an index value of 0.99 on the impact/benefits of KKN, indicating that KKN-PPM activities were categorized as very successful and benefited to the community, and gave an index value of 0.95 for the performance of KKN team, indicating that KKN-PPM team had sufficient competency and suitability knowledge with the program conducted.